2012
DOI: 10.5671/ca.2012361s.165
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of people with the perceived stress in Croatia: the CroHort Study

Abstract: A B S T R A C TThis study aimed to assess levels of stress in Croatian adult population using PSS, in a population study (Croatian Adult Cohort Health Study -CroHort

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
2
10
0
1
Order By: Relevance
“…Our patients had a mean level of stress of 19.1. This is similar to the findings in diabetic patients (19.35) ( 26 , 27 ) and higher than findings in healthy people in CAHS study (17.46 for men and 18.32 for women) (). Aside from the potential physiological impact, chronic stress may interfere with a person’s capacity to adhere to lifestyle-modifications that are essential to maintaining health.…”
Section: Discussionsupporting
confidence: 90%
“…Our patients had a mean level of stress of 19.1. This is similar to the findings in diabetic patients (19.35) ( 26 , 27 ) and higher than findings in healthy people in CAHS study (17.46 for men and 18.32 for women) (). Aside from the potential physiological impact, chronic stress may interfere with a person’s capacity to adhere to lifestyle-modifications that are essential to maintaining health.…”
Section: Discussionsupporting
confidence: 90%
“…The mean PSS (D (82) = 0.058), score was similar to the PSS score (18.32) previously described for females of Croatia, in a population study (CroHort) (44). Most of our respondents were females in their forties.…”
Section: Discussionsupporting
confidence: 53%
“…According to previous studies, females have consistently higher PSS scores. This was attributed to negatively scored items in the PSS; females often score higher and subjectively experience more stress than males and show a greater worry-disposition (39,(44)(45)(46)(47)(48)(49). However, nurses, who had experienced presenteeism, had a statistically significant higher PSS score (21.42).…”
Section: Discussionmentioning
confidence: 90%
“…The average stress level among Americans between 30 and 40 years of age is 13 . In the Croatian population of the same age group, the average level of stress is 16.925 in women and 15.964 in men . Warschburger and her collaborators showed on 187 parents of children suffering from AD that AD has a large impact on parental emotional stress, and a negative influence on the entire family, so they concluded that the medical treatment should include psychotherapeutic support for parents .…”
Section: Discussionmentioning
confidence: 99%
“…21 In the Croatian population of the same age group, the average level of stress is 16.925 in women and 15.964 in men. 22 Warschburger and her collaborators showed on 187 parents of children suffering from AD that AD has a large impact on parental emotional stress, and a negative influence on the entire family, so they concluded that the medical treatment should include psychotherapeutic support for parents. 23 Our study also confirmed that AD has a significant impact on the quality of family life, with the largest influence on the time spent caring for the sick child; household expenses; and parental mental health.…”
Section: Discussionmentioning
confidence: 99%